Citrus-orchard ground harbours a diverse, well-established and abundant ground-dwelling spider fauna - Monzó, C.; Mollá, O.; Vanaclocha, P.; Montón, H.; Melic, A.; Castañera, P.; Urbaneja, A. (Spanish Journal of Agricultural Research, 2011)
Ground-dwelling spider assemblages comprise one of the most representative predatory groups to be found in manycrops. There is some evidence of the role that ground-dwelling spiders play in controlling certain citrus pests; however, thereare almost no studies about the abundance and composition of this predatory group in citrus orchards. A three-year surveyconducted using pitfall traps in three citrus orchards in Eastern Spain yielded more than five-thousand ground-dwellingspiders belonging to more than 50 species and 20 families. Wandering families such as Lycosidae, Gnaphosidae andZodariidaewere the most numerous in terms of captures. The generalist predator Pardosa cribata Simon (Araneae: Lycosidae) was the most common species, representing a quarter of all captures, followed by Zodarion cesari Pekar. (Araneae: Zodariidae) and Trachyzelotes fuscipes (Koch) (Araneae: Gnaphosidae). Spiders were active throughout the year with a peak population in summer. The species abundance data for the three spider assemblages sampled fitted a log normal statistical model which is consistent with a well-established community. The presence of a cover crop provided higher abundance of alternative prey and consequently higher abundance and diversity of ground-dwelling spiders. This work demonstrates that the citrus-orchard ground harbours a diverse and abundant ground-dwelling spider fauna, which is also active throughout the year. A challenge for future studies will be to establish conservation management strategies for these predators, that will improve biological control of those citrus pests that inhabit or spend part of their life cycle on the orchard floor.